Hop Distance Symmetry Moderately Reflects Knee Biomechanics Symmetry During Landing But Not For Controlled Propulsions - Stefano Di Paolo; Naoaki Ito; Kayla D. Seymore; Haraldur B. Sigurðsson; Laura Bragonzoni; Stefano Zaffagnini; Lynn Snyder-Mackler; Karin Gravare Silbernagel (International Journal of Sports Physical Therapy)
# Background